128k views
0 votes
Help me it’s really important

Help me it’s really important-example-1
User Gosseti
by
4.3k points

1 Answer

1 vote

Answer:

Explanation:

Quadratic equation has been given as,


y=-x^(2) +6x+4

Converting this equation into vertex form,


y=-(x^(2)-6x)+4


y=-[x^(2)-2(3x)+9-9]+4


y=-[x^(2)-2(3x)+3^2]+4+3^2


y=-(x-3)^2+4+9


y=-(x-3)^2+13

By comparing this equation with the vertex form of a quadratic equation,

y = (x - h)² + k

Here, (h, k) is the vertex of the parabola.

Vertex of the parabola → x = 3, y = 13

Axis of symmetry → x = 3

User Sohan Soni
by
5.3k points